Of bears and ballots : an Alaskan adventure in small-town politics - Lende, Heather, 1959- (Algonquin Books of Chapel Hill, 2020)
"Following the 2016 presidential election, writer Heather Lende, inspired to take a more active role in politics, runs for assembly member in Haines, Alaska-and wins. But tiny Haines-a place accessible from the nearest city, Juneau, only by boat or plane-isn't the sleepy town it appears to be. From a bitter debate about the expansion of the fishing boat harbor to the matter of how to stop bears from rifling through garbage to the recall campaign that targeted three assembly members, including Lende, we witness the nitty-gritty of passing legislation, the lofty ideals of our republic, and how the polarizing national politics of our era play out in one small town"--